Epidendrum rasmussenii (Orchidaceae: Laeliinae), a new species from the Sierra Nevada de Santa Marta, Colombia - Gómez-Riaño, Miguel Ángel; Ayala, Elizabeth Santiago; Aguirre-Santoro, Julian; Castro, Cristian (Phytotaxa, 2025)
The Orchidaceae family is one of the most diverse within the Angiosperms, and Epidendrum is one of its largest genera. A new species of this genus, Epidendrum rasmussenii, is here illustrated, described, and compared with morphological and geographically similar species. This species was found in a cloud forest of The Sierra Nevada de Santa Marta (SNSM) in the Colombian Caribbean. It is similar to Epidendrum stenostachyum but differing by the red-carmin to yellow-green flowers with yellowish green towards apex in sepals and petals (vs. yellow-green, spotted with purple flowers), petals 5.6 × 0.4 mm, parallel to column and linear-filiform (vs. petals 6.8 × 1.3 mm, falcate, reflexed and linear-oblanceolate) and the lip reniform-cucullate and embracing apex column in natural position. (vs. lip widely triangular-ovate, flat).